How Do Transformational Leadership and Affective Trust Enhance Creativity? - Huynh Thi Thu, Suong; Pham, Minh (Ital Publication, 2024)
The pressure of competitive higher education has affected most universities, and whether the utilization of human capital as a resource to foster creativity, increase motivation, and boost innovation is an important topic to investigate. This study aims to explore the relationship between the elements of transformational leadership, affective trust, and intrinsic motivation and their impact on creativity to increase the performance of lecturers at Vietnamese universities, where most of them are also creators. Quantitative research is applied with data collected from full-time lecturers at Vietnamese universities from December 2023 to January 2024. The hypothesized correlations were investigated using structural equation modeling on a sample of 311 participants in Vietnam. The findings reveal substantial causal correlations between transformational leadership, affective trust, intrinsic motivation's determinants, and the creativity to improve performance and positive behavior from the lecturers' perspective. These results imply that leaders should focus on the prefix role of transformational leadership, which is the origin of affective trust, intrinsic motivation, and creativity, to raise the standard of higher education. In particular, affective trust needs more attention because it has the most vital mediating role in enhancing the impact of transformational leadership on lecturers' creativity. Doi: 10.28991/ESJ-2024-08-05-011 Full Text: PDF